Algebra and its applications - Rizvi, S. Tariq; Quardi, Murtaza A.; Ashraf, Mohammad, 1959-; Kazim, M. A., 1918-1980. (New Delhi : Narosa Pub. House, 2001)
Festschrift for Syed Mahammad Abdul Kazim Rizvi, 1918-1980, Indian mathematician; contributed papers presented at the Conference.
Includes bibliographical references.
Keywords: Algebra -- Congresses